Sponsoring True Feeling: Literacy, Parrhêsia, and Civic Mythos in the Writings of Detained Youth. (April 2016) - Catchings, Libby
This qualitative study traces different articulations of the public, emotional honesty, and economic advantage in the literacy sponsorship of detained writer Lil' Purp by The Beat Within, a publication for incarcerated youth and adults. Findings are compared to The Beat 's own account of Purp's progress, revealing a set of practices reminiscent of Socratic parrhêsia that revise understanding of literacy sponsorship by expanding it to a philosophical register. Because The Beat also becomes a site of affective solidarity among detained writers in a way that resists the directional logic of writing toward civic participation, the study supports thinking about affect in public writing not as a process that moves toward political action, but rather as action in the immediate space of its utterance and reception. Such findings have implications both for public writing pedagogy and for community-based literacy scholarship.